Perceptions of pesantren leaders towards Islamic moderation approaches in combating radicalism and terrorism - M Nurul Ikhsan Saleh (Cogent Arts & Humanities)
Islamic moderation has become a crucial response to radicalism and terrorism, reinforcing the understanding of Islam as a religion that upholds justice, balance, and peace. This study explores the pivotal role of pesantren (Islamic boarding school) leaders, who act as custodians of Islamic texts, in promoting Islamic moderation to counter radical interpretations that could lead to terrorism. Despite its significance, in-depth studies on Islamic moderation approaches remain limited. This qualitative research focuses on Yogyakarta and Central Java-provinces selected due to their significant pesantren networks and historical roles in fostering Islamic education and moderate religious thought in Indonesia. Using a case study design based on Robert K. Yin’s framework (2017), data were collected through in-depth interviews with 17 pesantren leaders, identified through snowball sampling. Four key themes emerged from the analysis: the understanding of Islamic moderation, approaches for implementing Islamic moderation within pesantrens, the roles of Islamic moderation in countering radicalism and terrorism, and approaches for cultivating Islamic moderation in broader Indonesian society. These findings offer valuable insights for policymakers, pesantren leaders, religious authorities, and educators in Islamic education, emphasizing the promotion of a balanced, context-sensitive, and peaceful interpretation of Islam.